2012
DOI: 10.1152/ajpgi.00485.2011
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK regulates Bax activity and apoptosis in enterocytes at baseline and after intestinal resection

Abstract: Increased apoptosis in crypt enterocytes is a key feature of intestinal adaptation following massive small bowel resection (SBR). Expression of the proapoptotic factor Bax has been shown to be required for resection-induced apoptosis. It has also been demonstrated that p38-α MAPK (p38) is necessary for Bax activation and apoptosis in vitro. The present studies were designed to test the hypothesis that p38 is a key regulator of Bax activation during adaptation after SBR in vivo. Enterocyte expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Our lab has recently developed an inducible, enterocyte-specific p38-alpha-deleted mouse model 22 . We have found that p38 MAPK is efficiently deleted in all enterocytes including the colonic epithelium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has recently developed an inducible, enterocyte-specific p38-alpha-deleted mouse model 22 . We have found that p38 MAPK is efficiently deleted in all enterocytes including the colonic epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings in mice with enterocyte-specific p38 deletion are consistent with its role as a tumor suppressor. Mice that lack p38 display increased proliferation and decreased apoptosis in the crypt cells of the small intestine 22 . Our results mirror work recently published by Otsuka et al who found that a constitutive, intestine-specific deletion of p38 led to a hyperproliferative state in the crypt compartment 24 .…”
Section: Introductionmentioning
confidence: 99%
“…H&E stained slides were analyzed for apoptotic bodies (pyknotic nuclei, condensed chromatin, and nuclear fragmentation) [18]. An apoptosis index was determined by counting the number apoptotic bodies found within 50 well-oriented crypts.…”
Section: Methodsmentioning
confidence: 99%
“…Each postoperative H&E stained sections were analyzed for apoptotic bodies (pyknotic nuclei, condensed chromatin) [14]. An apoptosis index was measured by counting the number apoptotic bodies found per 50 crypts.…”
Section: Methodsmentioning
confidence: 99%